Enhancing higher education curricula: A case study from the University of Waikato, New Zealand (UCL Press, 2018)
In 2014, the University of Waikato launched the Curriculum Enhancement Programme (CEP). As the leaders of this programme we have used auto-ethnography to reflect critically on our experience. Throughout the course of the CEP some things have gone well; others, in hindsight, have not gone so well and in retrospect we would have done them differently. This includes using more channels of communication, more frequently, especially with staff; getting all of Waikato's faculties to pull together more effectively as one institution; and working harder to increase students' opportunities for interdisciplinarity in teaching and research. These lessons, we hope, will be helpful for others also embarking on wide-scale curriculum change.